2022
DOI: 10.21203/rs.3.rs-1959917/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Survey-based Women Empowerment Index for Afghanistan (SWEIA): An Explanatory Analyses of the Afghanistan Demographic Health Survey 2015

Abstract: Background Although there are several scales to measure women empowerment, the multidimensionality of women empowerment introduced enormous challenges in the quantification and comparability of the results across different contexts. Therefore, in this study, we aimed to develop a country-specific index to measure women's empowerment in Afghanistan. Methods The data from the 2015 Afghanistan demographic health survey (ADHS) was used for the analysis. The dataset was randomly divided into two samples‒one for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Data analysis was conducted in four steps following the procedure from our previous paper [4]. First, the variables were extracted from PDHS 2017-18 dataset and either recoded or retained in their original forms for factor analysis (Table S1), then the dataset was randomly split into half using the STATA command "splitsample".…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Data analysis was conducted in four steps following the procedure from our previous paper [4]. First, the variables were extracted from PDHS 2017-18 dataset and either recoded or retained in their original forms for factor analysis (Table S1), then the dataset was randomly split into half using the STATA command "splitsample".…”
Section: Discussionmentioning
confidence: 99%
“…This study was a cross-validation of our previously developed index measuring women's empowerment in Afghanistan (SWEI-A) [4] to be used among married women aged 15-49 years in Pakistan. The original index was designed to measure women's empowerment in Afghanistan across seven domains; namely, labor force participation, attitude toward violence, decision-making, access to healthcare, literacy, age at critical life events, and property-owning; however, our analysis showed that the 6-factor model-excluding the property-owning-could better explain the woman empowerment among married women aged 15-49 years in Pakistan with an acceptable internal consistency (Cronbach's α = 0.70) and construct validity (SRSEA&SRMR < 0.05, CFI&TLI > 0.95).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations